2020
DOI: 10.3390/math8040567
|View full text |Cite
|
Sign up to set email alerts
|

Homomorphic Image and Inverse Image of Weak Closure Operations on Ideals of BCK-Algebras

Abstract: We introduce the notions of meet, semi-prime, and prime weak closure operations. Using homomorphism of BCK-algebras φ : X → Y , we show that every epimorphic image of a non-zeromeet element is also non-zeromeet and, for mapping c l Y : I ( Y ) → I ( Y ) , we define a map c l Y ← on I ( X ) by A ↦ φ − 1 ( φ ( A ) c l Y ) . We prove that, if “ c l Y ” is a weak closure operation (respectively, semi-prime and meet) on I ( Y ) , then so i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…for all x ∈ X, which shows that • satisfies the condition (13). For every x, y ∈ X, if x ≤ y then (x) ≤ (y), and so ( • )(x) = ( (x)) ≤ ( (y)) = ( • )(y).…”
Section: Example 38mentioning
confidence: 85%
See 2 more Smart Citations
“…for all x ∈ X, which shows that • satisfies the condition (13). For every x, y ∈ X, if x ≤ y then (x) ≤ (y), and so ( • )(x) = ( (x)) ≤ ( (y)) = ( • )(y).…”
Section: Example 38mentioning
confidence: 85%
“…For every x ∈ I (X), we havẽ 2 (x) =̃(¬¬ (x)) = ¬¬¬¬ (x) = ¬¬ (x) =̃(x) by (7). Hencẽsatisfies the condition (13). Let x, y ∈ I (X) be such that x ≤ y.…”
Section: Example 38mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature consists of several studies on BCKalgebras, importance seems to have been particularly attach to the ideal theory of BCKalgebras. For more details, recent studies [2][3][4][5][6][7][8][9][10] can be suggested in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Jun et al [14], [2], [3] have discussed soft set theory in residuated lattices. Jun and Park [17], Bordbar [1], [4], [5], [6], [7] and [8] studied applications of soft sets in ideal theory of BCK/BCI-algebras. Jun et al [15,16] introduced the notion of intersectional soft sets, and considered its applications to BCK/BCI-algebras.…”
Section: Introductionmentioning
confidence: 99%